Bimbingan Spiritual Selama Isolasi Mandiri Kepada Pasien UVHC UNISSULA - Fadzlurrahman, Fadzlurrahman; Thobroni, Ahmad (LP2M Institut Agama Islam Nazhatut Thullab Sampang, Indonesia, 2023)
In accordance with Article 1 paragraph 9 of Law No. 12 of 2012 concerning Higher Education, lecturers are mandated to fulfill the Tri Dharma of Higher Education, one of which is community service. Community service is an expression of the university's responsibility to society and the application of scientific knowledge within the community. As an entity within the realm of higher education, UNISSULA has an obligation to actively engage in community service activities with the aim of assisting the community in addressing various challenges. In this context, UNISSULA recognizes the emergence of new challenges within the community amid the widespread impact of the Covid-19 pandemic in Indonesia, namely the phenomenon of self-isolation. The handling of patients undergoing self-isolation often requires special attention. Therefore, UNISSULA deems it necessary to respond to this issue through community service activities. This community service report will document UNISSULA's concrete efforts to contribute to the community regarding the handling of self-isolation. Through a scientific approach and the application of knowledge, UNISSULA aims to provide relevant and effective solutions to address this issue. It is hoped that this activity can serve as a tangible example of the implementation of the Tri Dharma of Higher Education that has a positive impact on the welfare of the community around UNISSULA.